De-Europeanization in the Balkans. Media freedom in post-Milošević Serbia - Castaldo, Antonino (2019)
While the Europeanization literature has focused extensively on analysing progress towards the adoption of the European model, scant attention has been devoted to cases of resistance and contestation, which may lead to the emergence of a new phenomenon identified as de-Europeanization. In order to inquire on this phenomenon, a case study analysis will be applied to Serbian media freedom. Is this sector undergoing a process of de- Europeanization while the country is progressing toward full EU membership? The analysis demonstrates the recent consolidation of a de-Europeanizing trend, coinciding with the return to power of former Milošević ruling parties.